Atitude em relação a riscos e participação em discussões políticas: Um experimento sobre o papel da percepção de anonimato em redes sociais virtuais. - Rufino, Thales Pann Souza (2016)
E-participation, as complement to traditional political participation, represents a promise of revival of the civil society in the information age. Despite the reduced financial costs, e-participation is still in the early stages, if we consider the division that exists among those who participate and those who are outside of the online political debate. E-participation comes up against social risks derived from the expression of personal opinion, an example being ideological persecution. Anonymous communication on the Internet has been identified as dubious, because on the one hand it facilitates personal expression, but on the other it interferes with the debate, mainly because people lose their inhibitions. Therefore, an analysis of the relationship among risk attitudes, anonymity perception and intention of e-participation in virtual social networks was conducted. An experimental study was conducted by manipulating the perception of anonymity of professionals of a high-risk occupation in the public sector and measuring their risk attitudes and intentions of e-participation through Facebook. The results indicate that there is a strong association (R2 = 0,80; Β = 9,54; p-value < 0.01) between risk attitudes and intention of e-participation, and that this relationship is even stronger when the e-participation occurs in presence of greater perceived anonymity. Thus, it was observed that anonymity perception interacts with risk attitudes in an effect that moderates the relationship between the latter and intention of e-participation.